PENGUATAN DAN PENGEMBANGAN MODEL BISNIS BERKELANJUTAN GLEN CHOCO: PENDEKATAN TRIPLE LAYER BUSINESS MODEL CANVAS - Nur Lailin Jamilatun Nikmah; Illia Seldon Magfiroh (JSEP (Journal of Social and Agricultural Economics), 2022)
Cocoa plants are a leading plantation commodity that entirely exists in Indonesia. One of which is the highest production of Edel Cocoa in 2019 located at PTPN XII Kendenglembu, which has cocoa processing industry, namely Doesoen Kakao, and has great potential in improving the economy and social aspects. However, the weakness is using aluminum foil packaging, which is considered less environmentally friendly. The purpose of this study is to find out the mapping of the sustainable business model of the “Glen Choco” using TLBMC (Triple Layer Business Model Canvas) and decision using PMIA (Plus Minus Implication Analysis). The research method uses descriptive and analytic methods. The results show: 1) The results on TLBMC at the economic layer describe all elements, the environmental layer can’t describe the End of Life because the packaging isn’t environmentally friendly, the social layer can’t describe the Social Impact because it has no impact poor social society, 2) Decision on PMIA is the economic layer has a high score of 109 to strengthen the business model. The environmental layer has the lowest score of 70 to develop a business model, and the social layer has a high score of 96 to strengthen the business models.